Additive creativity: investigating the use of design for additive manufacturing to encourage creativity in the engineering design industry. Issue 4 (1st October 2020) - Prabhu, Rohan; Bracken, Jennifer; Armstrong, Clinton B.; Jablokow, Kathryn; Simpson, Timothy W.; Meisel, Nicholas A.
ABSTRACT: The capabilities of additive manufacturing (AM) enable designers to generate and build creative solutions beyond the limitations of traditional manufacturing. However, designers must also accommodate AM limitations to minimize build failures. Several researchers have proposed design tools and educational interventions for integrating design for AM (DfAM) in engineering design. However, there is a need to investigate the effect of DfAM training on industry professionals' use of these techniques and its subsequent effects on the creativity of their designs. In this paper, we present a workshop-based study in which industry professionals were sequentially introduced to opportunistic and restrictive DfAM. Participants were also given a DfAM task, with short idea generation sessions conducted between each content lecture. The participants' designs and their DfAM and creative self-efficacies were compared from before to after receiving DfAM training. The results show that DfAM training successfully increased participants' restrictive DfAM self-efficacy; however, no changes were seen in their opportunistic DfAM or creative self-efficacies. Further, the results show an increase in the uniqueness and overall creativity of the participants' designs, but no significant changes were seen in the initially high usefulness of the designs. These findings suggest that DfAM training presents an opportunity to encourage creative idea generation.